Dampak Limbah pada Ekosistem Alam di Karawang (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the impact of waste on natural ecosystems in the Karawang area, West Java. As one of the largest industrial estates in Indonesia, Karawang faces serious challenges related to industrial and domestic waste management. Poorly managed liquid and solid waste has polluted rivers, farmland, and forest areas, and disrupted the balance of local ecosystems. This study uses a qualitative approach through field observations, interviews with residents and related agencies, and secondary data analysis. The results of the study show that waste pollution has a direct impact on the decline in water quality, habitat damage, and the decline in biodiversity at several points in Karawang. In addition, the surrounding community also feels the impact through health problems and reduced agricultural yields. This study recommends the need to strengthen waste management regulations, increase supervision of industry, and involve the community in environmental conservation efforts. These findings are expected to be considered in the formulation of sustainable environmental policies in Karawang.